A NEW STAGE OF HISTORIOGRAPHIC UNDERSTANDING OF THE UKRAINIAN REVOLUTION PHENOMENON (the peer-review on the monograph: Oleksandr Reyent, Volodymyr Velykochy. The Ukrainian Revolution: Modern National Historiographical Discourse. Kyiv, Ivano-Frankivsk: Publishing House “Misto NV”, 2024. 396 p.) - UDOD, Oleksandr (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
the peer-review on the monograph: Oleksandr Reyent, Volodymyr Velykochy. The Ukrainian Revolution: Modern National Historiographical Discourse. Kyiv, Ivano-Frankivsk: Publishing House “Misto NV”, 2024. 396 p.